Alterações na assembleia de peixes antes e após a construção de barragens com trecho de vazão reduzida no rio das Antas, Rio Grande do Sul, Brasil. - Latini, João Dirço (2019)
The demand for electricity around the world has led several countries to construct and to plan more damming in rivers. Nowadays, even small and medium sized rivers are considered for the construction of dams, forming small to medium sized reservoirs, including a reduced flow stretch, once turbines are usually located downriver far from the dam. The purpose of this study was to investigate the effects of small to medium sized reservoirs on fish assemblages, using a Before-After Control-Impact (BACI) design, which includes sampling before and after dammings. Reservoirs were in the cascade of the Antas River (Castro Alves, Monte Claro and 14 de Julho dams and associated reservoirs). Specifically, alterations in the selected attributes (abundance, species richness, Shannon diversity index and evenness) and in the structure of fish assemblages were evaluated. Samples were conducted before and after reservoir filling, in three sampling stations of each reservoir, one located downstream (along the reduced flow stretch), another in the reservoir (lentic area) and the other above the reservoir (lotic stretch). For the collected data, in the three reservoirs, there were variation in abundance, species richness and Shannon diversity Index, always with greater values after the formation of the reservoirs. There were also variations for the sampling sites, with greater values of abundance and species richness downstream the dams. Variations in the structure of fish assemblages, due to the formation of the reservoirs, were also relevant. These variations were more intense in the station located below the dams, followed by the one located inside the reservoir and the one located upstream. The alterations appeared to be lessened because the hydrologic regime of the Antas River works as waves, in which, several times, the wave may pass over the dam, increasing water level downstream. The increases in species richness in the sites sampled seem to be a result of distinct processes. In the reduced flow stretch downstream dams, the increase may be attributed to the accumulation of fish due the obstacle represented by the dam. For the stations inside the reservoirs, the increases are due to samplings in the littoral zone during the trophic upsurge period; fish are known to inhabit the littoral, especially small characids. Finally, for the stations located upstream may be a result of the intense fish movements in this stretch.